EMPIRICAL STUDY ON LECTURER LEADERSHIP PRACTICES IN ONLINE LEARNING OF VOCATIONAL AVIATION COLLEGUE - Oke Hendra; Rini Sadiatmi (Journal of Airport Engineering Technology (JAET), 2023)
The aim of this study is to investigate the leadership exhibited by lecturers in the realm of online learning during Covid-19 pandemic. This research using a mixed methodology, both data collection and analysis were conducted to comprehensively address the research objectives. Primary data was gathered through the dissemination of questionnaires among selected cadets who served as respondents. Additionally, in-depth interviews were conducted with representatives from randomly chosen study programs. The acquired data was subsequently subjected to analysis employing simple statistical equations and a descriptive formula to calculate percentages. To augment the quantitative research findings, a triangulation process was implemented, integrating interview data with the concepts of lecturer leadership, which constituted the study's theoretical framework. The results of the study revealed that lecturers employed three key criteria, namely conceptual skills, human skills, and technical skills, in their leadership practices during the period of online learning amid Covid-19. The questionnaire results demonstrated that lecturers effectively employed various tactics within these three criteria to influence others, underscoring the inseparable connection between leadership and the lecturer's role. The research concludes that the leadership style exhibited by lecturers, as evidenced by these three criteria of skills and tactics, serves as a valuable reference for lecturers at higher education institutions.